Kajian Air Tanah Payau Menggunakan Metode Geolistrik Resistivitas dan Polarisasi Terinduksi Konfigurasi Schlumberger di Desa Dukuh dan Banyuripan Kecamatan Bayat Kabupaten Klaten - Rika Indah Lestari; Eddy Hartantyo (Jurnal Fisika Indonesia, 2025)
The presence of saline groundwater in several locations in Bayat District, Klaten is quite interesting to study considering that the location is far from sea. It is known from previous measurement from several dug wells and it is found that the presence of saline water forms an irregular spot pattern, especially in two villages; Banyuripan and Dukuh. Subsurface information related to these spot patterns needs to be studied in order to determine the distribution and know the depth of saline groundwater and the lithology of the rocks.The measurements were conducted using VES (Vertical Electrical Sounding) Induced Polarization methods to determine the resistivity and the chargeability of the rocks. The data acquisition conducted in 10 sounding points using the Schlumberger configuration with 100m current’s length. The measurement results were processed using IPI2Win software to obtain 1D profiles. This profiles then correlated to produce resistivity and chargeability cross sections. The data interpretation was connected with secondary data in the form of physical, geological and geochemical parameter data.The results of the study found that saline water began to appear at a depth of 1.08 m in accordance with the local water table. The spotting pattern in Banyuripan and Dukuh seen to be separated connate water.